Room to dream - Lynch, David 1946-2025; McKenna, Kristine (Random House, 2018)
"The extraordinary, highly anticipated memoir from visionary filmmaker David Lynch In this memoir, David Lynch, co-creator of Twin Peaks and writer and director of groundbreaking films like Eraserhead, The Elephant Man, Blue Velvet and Mulholland Drive, opens up about a lifetime of extraordinary creativity, the friendships he has made along the way and the struggles he has faced...sometimes successful, sometimes not...to bring his projects to fruition. Part-memoir, part-biography, Room to Dream interweaves Lynch's own reflections on his life with the story of those times, as told by Kristine McKenna, drawing from extensive and explosive interviews with ninety of Lynch's friends, family members, actors, agents, musicians, and collaborators. Lynch responds to each recollection and reveals the inner story of the life behind the art"...